The implication of major landslide to property market value: a study on the affected area and its surroundings (case study: Bukit Mewah, Bukit Antarabangsa) / Roba'yah Sawal - Sawal, Roba'yah (2010)
Natural disaster is often unpredictable but its' consequences is pretty much foreseeable. The victims will risk not only loss of assets but may also loose lives of the love ones. Loss of assets could be in terms of loss of uninsured properties or depreciation of its market values. The latter is pretty much applicable in real estate and property valuation. Landslide is the ranked second behind flood of the most occurred natural disaster in Malaysia. The property market in the affected area usually sees a depreciation of demand and thus later, in values. The study focuses on the market trend; before and after the landslide cases, and also its implication to the affected area and its surrounding. The study expects the demand of the properties in the affected area to be halted as soon as the tragedy occurred and in months a depreciation of value will be seen. However, as the study went on, the researcher only found out that the low demand of properties doesn't necessarily mean that the value will depreciated immediately.